Palynological study for nine cultivated species of Asteraceae family - Athia Nahi AL-Mashhadani; Israa Kreem Nasrullah; Aseel Fouad AL-Hussaini; Hind Ebraheem Ahmed (Journal of Madenat Alelem University College, 2014)
The current research included palynological study for nine ornamental cultivated species of Asteraceae family. The study included measurement the dimensions of pollen grains and there shape in polar view and equatorial view, sculpturing, colpi length and width, spines length and number of spines rows between colpi and exine thickness, the study showed variations in pollen grains characters for the studied taxa.